Negative Life Events and Coping Style among the Young Adults in a Highly Collective Community of Borneo - Komalavani, Subramaniam; Mai Sumiyati, Ishak (Faculty of Cognitive Sciences & Human Development, UNIMAS, 2016)
This qualitative study explored the differences in the interpretation of “negative life events” and the coping style among male and female young adults aged 21-25 in a highly collective community of Borneo. In-depth interviews were deployed, and pattern saturated at 5 males and 5 females. Thematic analysis was used to analyse the data. Finding shows that both gender, males and females, were most affected by self-image and identity crisis, implicating sensitivity for social acceptance/rejection, academic bullying, and friendship, family and and financial issues. Females were significantly affected by friendship problems and tended to deal with it using emotional-focused coping, such as, emotional release, whereas males reported rejection/one-sided love problems and tended to cope using action-focused coping style, such as, confronting, as well as action-focused release, such as, playing games. While the findings support the universal findings in the male-female differences in coping with negative events, this study found a unique difference in the coping style of the males to those of the lesser cohesive community - males in this community were found to be celebrating sharing of problems and emotional discomfort with close friends and family, as much as the females. This study suggests that careful considerations need to be given when generalizing the theory of emotional and social disconnectedness, in males in crisis in the highly cohesive community. Future research using mixed methodology can further explain the nature and generalizability of in-crisis males’ emotional and social connectedness in cohesive community, using a larger sample. Findings from this research would be useful to understand how our male and female youngsters in highly collective communities perceive life issues, and the pattern they choose in coping, and further assist in designing effective youth assistance and development programs.